(untitled) (Research, Society and Development, 2023)
This Work Aimed To Evaluate The Influence Of Water Restriction And Different Temperatures On The Physiological and biochemical performance of barley seedlings. The work was divided into two studies. First, osmotic potentials were tested to simulate water restriction in barley seeds submitted to different temperatures. The experiment was conducted under controlled conditions at temperatures of 20 and 35 ºc. The statistical design used was completely randomized, in a factorial scheme of 11 (cultivars) x 5 (osmotic potentials), with four replications. The first germination count, germination and dry mass of seedlings were evaluated. From study i, two cultivars with the best performance and one with the worst performance were selected. Afterwards, the experiments of the second study began. The experimental design used was completely randomized, in a factorial scheme 3 (cultivars) x 5 (osmotic potentials), with four replications. Antioxidant enzymatic activity, hydrogen peroxide, lipid peroxidation, total soluble sugars and amino acids were evaluated. Water restriction stress, associated or not with high temperature, affected germination, vigor and initial growth of cultivars. When subjected to water restriction and at 35 ºc, the seedlings showed high levels of enzymes, hydrogen peroxide, lipid peroxidation, amino acids and total soluble sugars.